(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The significance of the research is in understanding the degree of the influence of a neuro-linguistic programming educational curriculum on some mental talents in football for young people aged 13-15 years, which the researchers will create. The aim of the research was to identify the effect of the educational curriculum according to neuro-linguistic programming on some mental abilities in football for young people aged 13-15 years. The researchers used the experimental design with two experimental and control groups, due to its suitability to the nature of the problem. The researchers identified the research community by the intentional method, and they are the players of the football school in the Ghammas Youth Forum for Football, the junior category, who are accredited within the lists of the Football Sub-Confederation in Al-Diwaniyah Governorate for the 2021-2022 sports season, whose number is (50) players. The research sample was chosen at random by drawing lots, and it consisted of (50) participants, with (10) chosen for the reconnaissance sample and (40) chosen for the main sample, divided into two groups, experimental and control, each with (20) players. To make up 80% of the original community. As for the conclusions, the most important of them was the effectiveness of the proposed educational curriculum according to neuro-linguistic programming in developing the mental abilities (attention, perception, intelligence) of the research sample, and that mental ability (attention) is the most improved mental ability after applying the proposed educational curriculum, and that there is a positive relationship between capacity development Mental under research and components of neuro-linguistic programming. As for the suggestions, the foremost imperative of them was the have to utilize advanced technologies represented by the utilize of computers and to be seen by analysts within the field of mental capacities since they are characterized by precision and credibility and allow genuinely comes about rather than utilizing conventional implies such as (paper and write tests) which don’t donate the same precision of comes about as cutting edge strategies and implies. The use of the rehacom system in psychological exercises that works to develop most of the psychological variables such as (perception, attention, reaction) and other mental abilities, and the need for football coaches to pay attention to the youth groups, especially the youth, to increase and intensify the training courses related to the psychological aspect, which makes the players ready Permanent in terms of the psychological aspect.